Петро Румʼянцев-Задунайський та Катерина ІІ: особистісні відносини та їх вплив на становище Лівобережної України в другій половині XVIII ст. - Прокоп, Тарас Ігорович; Prokop, Taras I. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто особливості відносин між Катериною ІІ і графом, генерал-фельдмаршалом П. Румʼян-цевим та їх вплив на історичний розвиток українських земель, які опинилися під владою Російської імперії. Увагу зосереджено на ролі Катерини ІІ у прийнятті управлінських рішень П. Румʼянцевим на посаді генерал-губернатора Лівобережної України. Також проаналізовано еволюцію відносин між цими двома історичними постатями та з’ясовано, яке місце займав у них граф Г. О. Потьомкін. The article discusses the features of the relationship of Catherine the Great with P. Rumyantsev and it’s influence on the historical development of Ukrainian lands under rule of the Russian Empire in the second half of the XVIII century. The author focuses his attention on the role which Catherine the Great played in the administrative decisions of P. Rumyantsev when he was governor of Little Rus, as well as evolution of the relations between these two figures at different stages of historical development and the role graph Potemkin played in these relations. Why is the military commander was appointed to an administrative position, what guided him in the conduction of reforms on the territory of Little Rus, was he an independent or completely dependent on the will of the Empress's and, finally, what effect has the relationship between P. Rumyantsev and Catherine the Great on the development of Ukrainian lands? On these and other questions we’ll try to answer in this article.
Petr Rumyantsev and Catherine the Great. Personal Relationships and Their Impact on Development of the Left Bank Ukraine in the Second Half of the XVIII Century
Прокоп Т. Петро Румʼянцев-Задунайський та Катерина ІІ: особистісні відносини та їх вплив на становище Лівобережної України в другій половині XVIII ст. // Науковий вісник Східноєвропейського національного університету ім. Лесі Українки. Серія: історичні науки. Луцьк 2015. Вип. 5 (306). - С.10-15.
Keywords: P. Rumyantsev; Catherine the Great; Potemkin; the Russian Empire; Little Russian College; Російська імперія; Малоросійська колегія; П. Румʼянцев-Задунайський; Катерина ІІ; Г. О. Потьомкін